Emotional expressions beyond facial muscle actions. A call for studying autonomic signals and their impact on social perception - Kret, Mariska E. (Frontiers in Psychology, 2015)
Humans are well adapted to quickly recognize and adequately respond to another’s emotions. Different theories propose that mimicry of emotional expressions (facial or otherwise) mechanistically underlies, or at least facilitates, these swift adaptive reactions. When people unconsciously mimic their interaction partner's expressions of emotion, they come to feel reflections of those companions' emotions, which in turn influence the observer’s own emotional and empathic behavior. The majority of research has focused on facial actions as expressions of emotion. However, the fact that emotions are not just expressed by facial muscles alone is often still ignored in emotion perception research. In this article, I therefore argue for a broader exploration of emotion signals from sources beyond the face muscles that are more automatic and difficult to control. Specifically, I will focus on the perception of implicit sources such as gaze and tears and autonomic responses such as pupil-dilation, eyeblinks and blushing that are subtle yet visible to observers and because they can hardly be controlled or regulated by the sender, provide important veridical information. Recently, more research is emerging about the mimicry of these subtle affective signals including pupil-mimicry. I will here review this literature and suggest avenues for future research that will eventually lead to a better comprehension of how these signals help in making social judgements and understand each other’s emotions.